Darwinian Ethology and Naess’ Principles of Deep Ecology - Robert, Thomas (The Trumpeter, 2015)
The links between Darwinian theory and deep ecology seem, on face value, to be rather remote. Even though certain aspects of traditional interpretations of Darwinian theory can be correlated with the theoretical principles of deep ecology, it is necessary, in order to make stronger links apparent, to concentrate on a rarely addressed domain of Darwin’s thought, i.e. the study of animal behaviour. Darwinian ethology, based on principles that limit the importance of natural selection, is methodologically compatible with both theoretical and normative principles of deep ecology as defined by Naess. This article provides a definition of Darwinian ethology and explains its methodological compatibility with Naess’ principles of deep ecology.